ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGRAJIN GENTENG PRESS MINI DI DESA PEJATEN KECAMATAN KEDIRI KABUPATEN TABANAN - I DEWA GEDE GEDE RASTANA (Universitas Mahendradatta Denpasar, 2023)
The role of the small industry sector for mini press tile crafts in Pejaten Village, Kediri District, is expected to be able to contribute to regional economic growth and the development of the industrial sector, especially the mini press tile industry which can increase the income of the craftsmen, is one of the factors that play a role in absorption labor. The formulation of the problem in this study, whether the amount of production, labor, and working hours have a partial or simultaneous effect on income in the mini press tile craftsman industry, Pejaten Village, Tabanan Regency.The research sample was taken from all populations with the saturated sample method ,because the sampling of the population was carried out as a whole from the existing population as mini press tile entrepreneurs. The number of samples that were determined was the entire population of 35 entrepreneurs spread over several banjars in Pejaten Village, Kediri District, Tabanan Regency. The data analysis technique used is multiple linear regression analysis technique.Based on the results of the study, it can be explained that: (1) The amount of production has a real and positive effect on income in the mini press tile industry in Pejaten Village, Kediri District, because the tcount is greater than ttable or 6.789 1.695 and the significance value is smaller. Of 5% or 0.000 0.05. (2) Labor has a real and positive influence on income in the mini press tile industry in Pejaten Village, Kediri District, because the tcount is greater than ttable or 2,095 1,695 and the significance value is less than 5% or 0,044 0,05 . (3) Working hours have a significant and positive effect on the value of income in the mini press tile industry in Pejaten Village, Kediri District, because the tcount is greater than ttable or 2,056 1,695 or the significance is less than 5% or 0,038 0,05 . (4) The amount of production (X1), labor (X2), and working hours (X3) together have a real and positive influence on income in the mini press tile industry in Pejaten Village, Kediri District, this can be seen from the value of the Fratio is greater than the Ftable or 37.453 2.910. Likewise, when viewed from the significance value, which is 0.000, it is smaller than 0.05 (5%) or 0.000 0.05. Based on the results of the analysis of determination, the percentage of the contribution of the influence of the independent variable (amount of production, labor and working hours) on the dependent variable (income) of 78.4%. While the remaining 21.6% is influenced or explained by other variables that are not included in this research model.